Increasing Active Learning in Large, Tightly Coordinated Calculus Courses. Issue 3 (28th May 2021) - Miller, E.; Fowler, J.; Johns, C.; Johnson, J.; Ramsey, B.; Snapp, B.
ABSTRACT: We discuss a decade of initiatives to improve the teaching and learning of calculus at The Ohio State University. Calculus at OSU is taught in lecture/recitation format with large lectures and is tightly coordinated, so all innovations had to occur within that framework. We show how many smaller projects built upon one another to create a larger transformation, and how these projects were each situated within the culture of the department. Projects discussed include conversion to an open-source textbook, development of an online and hybrid version of the course, introduction of recitation worksheets, use of a polling system in lecture, professional development for instructors, and an iPads for instruction initiative. We detail the importance of a large team working together for change and the role data has played in our efforts. Finally we present lessons learned that we hope are helpful to other departments undertaking similar efforts.